A Secondary School Accounting Teacher Perceptions on Student Assessment in Formal Education in Nepal - Shiva Dutta Chapagai (Mauve Journal De Leardu, 2024)
Remittances are very crucial in the world economy and are a significant source of income to developing countries. Not only are they a source of financial life line to households, they are also a major boost to economic growth in recipient countries. Remittances have come to play a major role in the social and economic development by offering investment opportunities, improving household consumption, alleviating poverty and empowering women. This paper shall examine how remittance income can empower women in Nepal. The research design applied was a descriptive cross-sectional study design which uses a structured questionnaire as the source of primary data. The responses were measured using a five-point Likert scale, and the analysis of the data was done using descriptive statistics, such as the mean, t -test, and percentages. The findings reveal that remittances have a significant impact, or increase on the financial autonomy of women, their educational access, medical services, and their control or influence in the households. Besides, they promote community development and alleviation of poverty. T-stats and weak p-stats affirm the congruence of respondents about such impacts. The results highlight the significance of adopting policies and specific interventions that will help optimize the benefits of remittances and make them a sustainable means of women empowerment and the development of the entire society.